2012
DOI: 10.1029/2012jd017449
|View full text |Cite
|
Sign up to set email alerts
|

Past and future wind climates over the contiguous USA based on the North American Regional Climate Change Assessment Program model suite

Abstract: [1] Multiple descriptors of wind climates over the contiguous USA from a suite of thirteen simulations conducted with five Regional Climate Models (RCMs) nested within reanalysis data and four Global Climate Models are evaluated relative to the North American Regional Reanalysis (NARR) and independent observations. Application of the RCMs improves 'forecasts' of wind climates during 1979-2000 relative to the driving reanalysis, and the RCMs exhibit some skill in depicting historical wind regimes. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 71 publications
2
38
1
Order By: Relevance
“…Then, using typical hub heights and a common turbine power curve, they found that the power produced in the summer could decrease by about 40%; although it should be noted that this is a worst case value, estimated under the GCM projection uncertainties discussed previously. Pryor et al [21] used a suite of thirteen simulations from a combination of four Regional Climate Models (RCMs) nested in reanalysis data and four global climate models. These simulations were compared to independent observations and the North American Regional Reanalysis (NARR) over the contiguous United States.…”
Section: Previous Attempts To Characterize the Future Wind And Solar mentioning
confidence: 99%
“…Then, using typical hub heights and a common turbine power curve, they found that the power produced in the summer could decrease by about 40%; although it should be noted that this is a worst case value, estimated under the GCM projection uncertainties discussed previously. Pryor et al [21] used a suite of thirteen simulations from a combination of four Regional Climate Models (RCMs) nested in reanalysis data and four global climate models. These simulations were compared to independent observations and the North American Regional Reanalysis (NARR) over the contiguous United States.…”
Section: Previous Attempts To Characterize the Future Wind And Solar mentioning
confidence: 99%
“…The occurrence of intense and extreme wind speeds (defined here as wind speeds in excess of 10 m s 21 at 10 m AGL and above the 95th percentile, respectively) is associated with a range of ecological impacts [e.g., seed dispersal (Bullock et al 2012), forest health (Blennow et al 2010;Gardiner et al 2000;Peltola et al 2010), and crop damage (Moore and Osgood 1985)] and with impacts on major energy, transportation, and built-environment infrastructure (Della-Marta et al 2010;Pryor and Barthelmie 2013a,b;Zhou et al 2002). A further motivation for this analysis derives from evidence of divergent trends in the central tendency and upper tail of the wind speed distribution as observed in historical data (Cusack 2013;Pryor et al 2009). Thus, improved understanding of the magnitude and spatial coherence of extreme and intense wind events is essential for diagnosing the causes of damaging winds and for projecting their impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, improved understanding of the magnitude and spatial coherence of extreme and intense wind events is essential for diagnosing the causes of damaging winds and for projecting their impacts. Therefore, improved understanding of the causes of damaging winds is key to assessing how such events may alter under climate nonstationarity (Cheng et al 2014;Pryor and Barthelmie 2014;Pryor et al 2012). Decreases in mean wind speeds have been observed in some regions to be linked to increases in local/regional roughness and/or changes in cyclone storm tracks (Vautard et al 2010), and they have, in some instances, been associated with increases in extreme and intense wind speeds that result from intensification of the hydrological cycle (Huntington 2006) and increased latent heat release in clouds associated with frontal systems such as those studied herein.…”
Section: Introductionmentioning
confidence: 99%
“…However, analyses of wind speeds from the NARCCAP suite provide clear indication of added value in applying RCMs relative to the driving AOGCM (Pryor et al 2012a) and there is some indication that adopting a non-hydrostatic formulation even at these spatial scales does 'improve' model simulations of extreme wind speeds (Pryor et al 2012b).…”
Section: Added Valuementioning
confidence: 97%